2016
DOI: 10.1515/fhort-2016-0011
|View full text |Cite
|
Sign up to set email alerts
|

Cultivar effect on the sweet cherry antioxidant and some chemical attributes

Abstract: This research was carried out to evaluate the phenolic composition, antioxidant capacities, sugars and organic acids content of sweet cherry cultivars

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…The total content of polyphenols has a particular importance in determining the sweet cherries' taste and flavour, along with an antioxidant role with anticancer effect (Chaovanalikit and Wrolstad, 2004). Other studies reported large variations of polyphenols in investigated sweet cherry cultivars (Kim et al, 2005;Melicháčová et al, 2010;Skrzyński et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The total content of polyphenols has a particular importance in determining the sweet cherries' taste and flavour, along with an antioxidant role with anticancer effect (Chaovanalikit and Wrolstad, 2004). Other studies reported large variations of polyphenols in investigated sweet cherry cultivars (Kim et al, 2005;Melicháčová et al, 2010;Skrzyński et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…According to Petanidou sorbitol is a frequent constituent of Mediterranean nectars. Also, if it can be found in the fruit, it improves the sweet taste and texture of the mesocarp . Regarding maltose, it pretty rare or absent in nectars.…”
Section: Resultsmentioning
confidence: 99%
“…Also, if it can be found in the fruit, it improves the sweet taste and texture of the mesocarp. [53] Regarding maltose, it pretty rare or absent in nectars. As reported by Tinti and Nofre [54] maltose tastes sweet to honeybees, but usually is less attractive for them than sucrose.…”
Section: Quantitative Phenolic Profile Of Sour Cherry Nectarmentioning
confidence: 99%
“…In vitro antioxidant assays, such as 2,2’-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS), 2,2-diphenyl-1-picrylhydrazyl (DPPH), ferric reducing ability of plasma (FRAP), oxygen radical absorbance capacity (ORAC) and nitric oxide (NO) assays, have demonstrated that sweet cherries display a high capacity to capture free radicals [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. Moreover, studies reported that sweet cherry extracts inhibit lipid peroxidation [ 44 , 45 ] and the oxidation of human low-density lipoprotein (LDL) [ 40 , 46 , 47 ] and liposomes [ 47 , 48 ].…”
Section: Sweet Cherries and The Hallmarks Of Cancermentioning
confidence: 99%